1999
DOI: 10.1046/j.1365-8711.1999.02264.x
|View full text |Cite
|
Sign up to set email alerts
|

Meteoroid stream identification: a new approach -- I. Theory

Abstract: A B S T R A C TWe introduce a new approach to meteoroid stream identi®cation, based on a distance function involving four geocentric quantities that are directly linked to observations; the new distance function is thus de®ned in a space that has as many dimensions as the number of independently measured physical quantities, at variance from the conventional orbital similarity criterion of Southworth & Hawkins. Two of the new variables turn out to be near-invariant with respect to the principal secular perturb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
89
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(89 citation statements)
references
References 16 publications
(21 reference statements)
0
89
0
Order By: Relevance
“…A94, page 5 of 7 A&A 598, A94 (2017) Valsecchi et al (1999) used the quantities of U and cos θ to identify meteor showers with orbits having different q, e, i, Ω and ω as possibly originating from the same body, due to secular perturbations on the same meteoroid stream. Here, U is the geocentric velocity of the meteoroids when crossing the Earth's orbit…”
Section: Criteria Of Orbital Similaritymentioning
confidence: 99%
See 1 more Smart Citation
“…A94, page 5 of 7 A&A 598, A94 (2017) Valsecchi et al (1999) used the quantities of U and cos θ to identify meteor showers with orbits having different q, e, i, Ω and ω as possibly originating from the same body, due to secular perturbations on the same meteoroid stream. Here, U is the geocentric velocity of the meteoroids when crossing the Earth's orbit…”
Section: Criteria Of Orbital Similaritymentioning
confidence: 99%
“…As a result of developing the distance function concept, Valsecchi et al (1999), Jopek et al (1999Jopek et al ( , 2003 have suggested the absolutely new criterion of orbital similarity, based on the known integrals of the restricted circular three body problem.…”
Section: Criteria Of Orbital Similaritymentioning
confidence: 99%
“…Several empirical metrics in orbital elements are defined for finding Taurid parent bodies that cluster using asteroids and comets Valsecchi et al 1999;Jopek et al 2008). Based on different criteria, like "D-criterion", several authors have determined the asteroids belonging to TC Babadzhanov 2001;Babadzhanov et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Several similarity functions have been proposed: D S H the orbital D-criterion introduced by Southworth and Hawkins (1963), its modifications by Drummond (1981), Jopek (1993), Valsecchi et al (1999), and Jenniskens (2008) and the D V function defined in the domain of the vectorial heliocentric orbital elements (Jopek et al (2008)). The threshold, D c is used to test the similarity among two…”
Section: Introductionmentioning
confidence: 99%